1996
DOI: 10.2331/fishsci.62.624
|View full text |Cite
|
Sign up to set email alerts
|

Protein Sparing Effect of Lipids in Diets for Fingerlings of Gilthead Sea Bream

Abstract: A feeding trial was conducted to determine the sparing effect of lipids on dietary protein in gilthead sea bream Sparus aurata fingerlings, by combining different levels of protein (42-58%) at two lipid lev els (9, 15%) in the diets. Sardine meal and sardine oil were employed as the main source of dietary pro tein and lipid, respectively. Weight gain and specific growth rate of fish improved for each dietary pro tein level when lipids were increased in diets from 9% to 15%, up to 52% dietary protein. There was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
59
2
10

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(91 citation statements)
references
References 14 publications
20
59
2
10
Order By: Relevance
“…This shows that with the increase in dietary lipid level, the carcass lipid content also goes on increasing. Similar trend has also been found by [11]. Similarly, Du et al [12] reported that body lipid content of grass carp increased with increase in dietary lipid levels, indicating that this fish could deposit lipid in the muscle.…”
Section: Proximate Compositionsupporting
confidence: 75%
“…This shows that with the increase in dietary lipid level, the carcass lipid content also goes on increasing. Similar trend has also been found by [11]. Similarly, Du et al [12] reported that body lipid content of grass carp increased with increase in dietary lipid levels, indicating that this fish could deposit lipid in the muscle.…”
Section: Proximate Compositionsupporting
confidence: 75%
“…The use of diet protein is related to both protein level and availability of non-protein energy sources. A number of studies have been conducted to determine the optimal diet protein level for some sparids fishes (Santinha et al 1996;Vergara et al 1996;Tibaldi et al 1996;Sá et al 2006) and have estimated 40-50% as the optimal diet protein level in terms of growth performance. Being the muscle the final product in fish farming it is surprising that there is very little work specifically linking diet protein level to muscle growth dynamics in juveniles.…”
Section: Introductionmentioning
confidence: 99%
“…The reaction of a given species to various lipid levels can also depend on developmental stage. Lipid levels ranging from 12 to 20% were not seen to have an effect on the growth rates of larval gilthead sea bream Sparus aurata (Salhi et al, 1994), but increasing lipid levels from 9 to 15% significantly improved the growth rate of juvenile stages of this species (Vergara, 1996). Percid fishes are particularly sensitive to oxidised lipids in feed.…”
Section: Discussionmentioning
confidence: 90%